Proteoglycan-specific molecular switch for RPTPσ clustering and neuronal extension. - Coles, C; Shen, Y; Tenney, A; Siebold, C; Sutton, G; Lu, W; Gallagher, J; Jones, E; Flanagan, J; Aricescu, A (2011)
Heparan and chondroitin sulfate proteoglycans (HSPGs and CSPGs, respectively) regulate numerous cell surface signaling events, with typically opposite effects on cell function. CSPGs inhibit nerve regeneration through receptor protein tyrosine phosphatase sigma (RPTPσ). Here we report that RPTPσ acts bimodally in sensory neuron extension, mediating CSPG inhibition and HSPG growth promotion. Crystallographic analyses of a shared HSPG-CSPG binding site reveal a conformational plasticity that can accommodate diverse glycosaminoglycans with comparable affinities. Heparan sulfate and analogs induced RPTPσ ectodomain oligomerization in solution, which was inhibited by chondroitin sulfate. RPTPσ and HSPGs colocalize in puncta on sensory neurons in culture, whereas CSPGs occupy the extracellular matrix. These results lead to a model where proteoglycans can exert opposing effects on neuronal extension by competing to control the oligomerization of a common receptor.